Improving Students’ Listening Comprehension through New Vocabulary Learning - Purba, Christian Neni (Budapest International Research and Critics University, 2020)
This research is about the improving student’s comprehension in listening through introducing the new vocabulary. The background of research was based on phenomenon that students had in the classroom at FKIP UHN. They had problems in listening one of the them was lack of vocabulary. This research focused on the way to improve the students’ comprehension in listening.This research applies classroom action research, aimed to describe the improvement process of teaching learning listening. t used intimate language style. The result of this study found that in the pre cycle the students’ average score is 57. 82%. In the first cycle the students’ average score is 68.38. In the second cycle the students’ average score is 72. The average of students score was always increasing. It means that improvement of students listening comprehension increase each cyles by learning new vocabulary.